2021
DOI: 10.3389/fcell.2021.648098
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Regeneration Capacity of Extracellular Vesicles Isolated From Bone Marrow-Derived and Adipose-Derived Mesenchymal Stromal/Stem Cells

Abstract: Mesenchymal stem cell (MSC)-based therapies have demonstrated tissue repair and regeneration capacity in various preclinical models. These therapeutic effects have recently been largely attributed to the paracrine effects of the MSC secretome, including proteins and extracellular vesicles (EVs). EVs are cell-secreted nano-sized vesicles with lipid bilayer membranes that facilitate cell–cell signaling. Treatments based on MSC-derived EVs are beginning to be explored as an alternative to MSC transplantation-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 153 publications
(225 reference statements)
0
27
0
Order By: Relevance
“…ASCs have been widely used as a source of EV production because of their plentifulness and accessibility compared with bone marrow-derived MSCs (BM-MSCs), while it has a similar ability to differentiate into mesodermal linage cells (Gimble et al, 2007;Maqsood et al, 2020). Treatments based on EVs from adipose tissue-derived stem cells (ASC-EVs) have been investigated in tissue repair and disease models (Liu & Holmes, 2021). Two studies reported that ASC-EVs increased the osteogenic differentiation and bone formation in the calvarial defect model (S. Chen, Tang, et al 2019;W.…”
Section: Introductionmentioning
confidence: 99%
“…ASCs have been widely used as a source of EV production because of their plentifulness and accessibility compared with bone marrow-derived MSCs (BM-MSCs), while it has a similar ability to differentiate into mesodermal linage cells (Gimble et al, 2007;Maqsood et al, 2020). Treatments based on EVs from adipose tissue-derived stem cells (ASC-EVs) have been investigated in tissue repair and disease models (Liu & Holmes, 2021). Two studies reported that ASC-EVs increased the osteogenic differentiation and bone formation in the calvarial defect model (S. Chen, Tang, et al 2019;W.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomebased therapies are currently being studied to specifically silence the immune system toward the graft. Several cell types are candidates for sources of exosomes: mesenchymal stem cells, regulatory T cells, M2 macrophages and immature dendritic cells, which are well-known immunoregulatory cells [141][142][143][144].…”
Section: Exosomes In Transplantationmentioning
confidence: 99%
“…The ability to sense changes is also translated in vitro , where cell culture conditions ( 219 ) or exposure to licensing strategies ( 275 ) can impact the secretome, highlighting plasticity and ability to adapt and respond to surroundings ( 274 , 276 ). The so-called MSC secretome is composed of small molecules, chemokines, cytokines, growth factors, as well as EVs ( 277 , 278 ). The literature has shown striking differences in the composition of MSC-secretome depending on the cell source.…”
Section: Biological Properties Of Mscs Derived From Different Tissue Sourcesmentioning
confidence: 99%